PENINGKATAN MASA SIMPAN LEMPOK DURIAN UKURAN KECIL DENGAN MENGGUNAKAN EMPAT JENIS KEMASAN - Budi Santoso; Amin Rejo (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The objective of this research was to predict shelf life of lempok durian (bite size) that was packed by four kinds of packaging and using ASLT method. The research was arranged in ASLT and Complete randomized design with four treatments. Each treatment was replicated three times. The treatments use four packaging. The packaging was wrapping, parchment paper, Aluminium foil, aluminium foil and wrapping. The parameters were FFA (Free Fatty Acid), water content, total plate count, and visual observation. The result showed that lempok durian that was packed by four kinds of packaging had significant effect on characteristic of lempok durian during storage.Lempok durian packaged with parchment paper could increase the shelf life of lempok durian for 191 days, lempok durian packaged with alumunium foil could increase the shelf life of lempok durian for 113 days, lempok durian packaged with alumunium foil and wrapping could increase the shelf life of lempok durian for 122 days, lempok durian packaged with wrapping could increase the shelf life of lempok durian for 33 days. The best of treatments was lempok durian packaged with parchment paper because could increase the shelf life of lempok durian for 191days.